Perspektif masyarakat di Kota Padang terhadap rencana kebijakan redenominasi mata uang rupiah - Marshely Zulhaisa; Syafruddin Karimi; Endrizal Ridwan (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to examine the perceptions of the people in the city of Padang on the plan to redenominate the rupiah currency and see how the redenomination's impact the economy. The data used are primary by distributing questionnaires to the community according to sub-districts in Padang City, where the data are grouped based on the highest level of education attained. The data analysis method in this research is qualitative by using descriptive analysis of the frequency and descriptive analysis of cross-tabulations (crosstabulation). From the results of this study, it was found that some people did not agree with the redenomination policy because they did not understand this policy. From the results of the crosstabulation descriptive analysis, it can be seen that there is a relationship between the level of education and the perception of the impact of redenomination on the exchange rate and consumption patterns. Meanwhile, there is no relationship between education level and knowledge of redenomination, opinion on redenomination policy, and perceptions about the impact of redenomination on inflation and savings. Keywords: Community perspective, Redenomination, Sanering, Inflation, Exchange rate